On numerical investigation of nusselt distribution profile of heat sink using lateral impingement of air jet - Umair, Siddiqui; Ansari, Emad; Khan, Sher Afghan; Patil, Rajesh (Penerbit Akademia Baru, 2019)
The looming world of electronic packaging systems and material processing industries needs a non-uniform cooling of product in order to meet the demanding challenges. Generally, impinging air jet over heat sink is used for its cooling. As far as the nonuniformity in the cooling rate is concerned, lateral geometric thickness and thermophysical properties of target surface play a vital role in its contribution. Study of previous research works avails an immense gap in the area of characteristic heat transfer augmentation study. Looking into this, the present work takes an assignment to justify the measure of nonuniformity in the Nusselt distribution curve and its dependency on geometric thickness. Also, the dependency of Reynolds number and nozzle to the target spacing in designing the Nusselt profile is observed graphically. It is seen that after a particular critical thickness of 0.5 mm the Nusselt profile seems to be saturated and constant throughout the radial distance. Not only that, an inverse variation is observed between the magnitude of area-averaged Nusselt number and non-dimensional geometric thickness (t/d). This inverse variation is applicable up till a particular critical value of a non-dimensional geometric thickness of 0.05.